2005
DOI: 10.1161/circulationaha.104.523563
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Occlusive Coronary Atherosclerosis, Myocardial Infarction, Cardiac Dysfunction, and Premature Death in Scavenger Receptor Class B Type I-Deficient, Hypomorphic Apolipoprotein ER61 Mice

Abstract: Background-Normal chow (low fat)-fed mice deficient in both the HDL receptor SR-BI and apolipoprotein E (SR-BI/apoE dKO) provide a distinctive model of coronary heart disease (CHD). They exhibit early-onset hypercholesterolemia characterized by unesterified cholesterol-rich abnormal lipoproteins (lamellar/vesicular and stacked discoidal particles), occlusive coronary atherosclerosis, spontaneous myocardial infarction, cardiac dysfunction, and premature death (Ϸ6 weeks of age). Mice in which similar features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
163
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(193 citation statements)
references
References 34 publications
21
163
1
8
Order By: Relevance
“…SR-BI KO/ApoeR61 h/h mice have low, rather than no, plasma apoE, rendering them susceptible to diet-induced hyperlipidemia, atherosclerosis and CHD. 23,46 Taken together with our earlier studies, [2][3][4]21 this work supports the suggestion that occlusive coronary atherosclerosis is directly responsible for ischemia-induced myocardial infarction, which in turn leads to cardiac dysfunction and premature death, a pathologic process closely resembling that in human CHD. Because rapid onset occlusive coronary arterial atherosclerosis, (to date, occlusive thrombi have not been observed in these mice [unpublished data, 2005]), associated MI does not usually accompany the aortic atherosclerosis seen in other common murine models of hyperlipidemia, 24,47-51 the dKO mouse, and its variant, SR-BI KO/ ApoeR61 h/h mice, 23 provide attractive small animal models of human occlusive atherosclerotic CHD for genetic and pharmacological studies of the mechanisms underlying the most common causes of heart disease and preclinical testing of new therapeutic strategies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…SR-BI KO/ApoeR61 h/h mice have low, rather than no, plasma apoE, rendering them susceptible to diet-induced hyperlipidemia, atherosclerosis and CHD. 23,46 Taken together with our earlier studies, [2][3][4]21 this work supports the suggestion that occlusive coronary atherosclerosis is directly responsible for ischemia-induced myocardial infarction, which in turn leads to cardiac dysfunction and premature death, a pathologic process closely resembling that in human CHD. Because rapid onset occlusive coronary arterial atherosclerosis, (to date, occlusive thrombi have not been observed in these mice [unpublished data, 2005]), associated MI does not usually accompany the aortic atherosclerosis seen in other common murine models of hyperlipidemia, 24,47-51 the dKO mouse, and its variant, SR-BI KO/ ApoeR61 h/h mice, 23 provide attractive small animal models of human occlusive atherosclerotic CHD for genetic and pharmacological studies of the mechanisms underlying the most common causes of heart disease and preclinical testing of new therapeutic strategies.…”
Section: Discussionsupporting
confidence: 86%
“…As previously reported, higher lipoprotein surface to core lipid ratios are associated with greater atherogenic potential in different SR-BI-deficient models of CHD. 4,23 Thus, we did not observe substantial HL-dependent differences in the lipoproteins. Further studies are necessary to determine whether subtle differences in lipoprotein structures caused by HL deficiency, or if HL-dependent changes in lipoprotein metabolism distinct from changes in particle structure (eg, as a consequence of the lipoprotein binding activity of HL), 29 were responsible for the striking effects on atherosclerosis in dKO mice.…”
Section: Effects Of Hepatic Lipase Deficiency On Aortic Root and Occlmentioning
confidence: 52%
See 2 more Smart Citations
“…Numerous studies have demonstrated that both SR-BI and apoE are important in minimizing atherosclerotic lesion development. Single-gene deletion of either apoE (7,8) or SR-BI (9) in mice accelerates atherosclerotic lesion development, whereas low-level transgenic expression of either SR-BI (3) or apoE (10,11) reduces the extent of atherosclerosis. Furthermore, the combined deficiency of SR-BI and apoE produces the only mouse model of accelerated and fatal atherosclerosis.…”
mentioning
confidence: 99%